Atypical squamous cells of undetermined significance ASC-US in cervical epithelium stained with H&E stain and AgNOR stain - Faisal, Ghasak Ghazi (2020)
2 microscopic views of cervical epithelium showing Atypical squamous cells of undetermined significance (ASC-US) staind with hematoxilin and eosin and AgNOR stain